Bone Spreading and Standardized Dilation of Horizontally Resorbed Bone: Technical Considerations - Nishioka, Renato Sussumu [UNESP]; Souza, Francisley Avila [UNESP] (Lippincott Williams & Wilkins, 2009)
The uses of a new bone spreading technique with simultaneous implant placement are discussed. The spreading system is an alternative technique to Summers' osteotome. Specific screw designs (spreader) served to laterally compress the bone to increase the cancellous density adjacent to the site. The spreader achieved a controlled and standardized dilation of horizontal bone. The advantages, material selection, and the application of this new procedure are detailed. (Implant Dent 2009; 18:119-125)
Keywords: dental implant; deficient alveolar bone width; ridge expansion